Development of chemotherapy and significance of conversion surgery after chemotherapy in unresectable pancreatic cancer - Furuse, Junji; Shibahara, Junji; Sugiyama, Masanori (Journal of hepato-biliary-pancreatic sciences, 2018)
While surgery currently remains the only potentially curative treatment available for pancreatic cancer, only 20% to 30% of patients have resectable disease at diagnosis. Recently, with the introduction of intensive chemotherapy regimens such as oxaliplatin, irinotecan, fluorouracil plus leucovorin (FOLFIRINOX) and gemcitabine plus nab‐paclitaxel, for the treatment of unresectable pancreatic cancer, the antitumor activity and overall survival in patients with pancreatic cancer have dramatically improved. These advances in intensive chemotherapy have led to the possibility of conversion of unresectable disease to resectable disease, and it has been reported that more than 20% of pancreatic cancer patients with unresectable locally advanced disease at diagnosis undergo successful conversion surgery after FOLFIRINOX therapy. In metastatic pancreatic cancer, resection for the primary lesion of pancreatic cancer may show some benefits for some patients with complete resolution of metastases by chemotherapy. Furthermore, surgical resection in some patients with only a few metastases, so‐called oligometastases, have also been reported. Conversion surgery is becoming increasingly possible with the introduction of intensive chemotherapies, however, the actual clinical benefits of resection in such cases has not yet been sufficiently investigated. The long‐term safety, feasibility and outcomes still need to be investigated in well‐designed, multi‐institutional studies on a large number of patients. Highlight Furuse and colleagues review recent developments in the treatment of unresectable pancreatic cancer. The introduction of intensive chemotherapy regimens has dramatically improved antitumor activity and overall survival in pancreatic cancer patients, making conversion surgery increasingly possible. The long‐term safety, feasibility and outcomes, however, remain to be investigated in multi‐institutional studies.